Clinical features of diffuse large B‐cell lymphoma with polyploidy. Issue 1 (21st November 2016) - Shimono, Joji; Miyoshi, Hiroaki; Seto, Masao; Teshima, Takanori; Ohshima, Koichi
Abstract : Polyploidy, defined as more than two sets of homologous chromosomes, is found in a variety of malignant tumors and is thought to be related to disease pathogenesis. However, there have been no studies that have investigated polyploidy in diffuse large B‐cell lymphoma (DLBCL). Here we reviewed clinicopathological features of 16 cases of DLBCL with polypoidy, which was defined as DLBCL with either near‐tetraploid or greater number of chromosomes as detected by the G‐band method. The frequency of polyploid DLBCL was 2.9 % (16/544), including 15 near‐tetraploid and one near‐pentaploid case. CD5, CD30 and EBER positive cases were 13 % (2/16), 13 % (2/16) and 6 % (1/16), respectively. Bcl2 positive cases were 75 % (12/16). The numbers of huge and multinucleated cells were higher in polyploid than in non‐polyploid DLBCL ( P = 0.0029 and P < 0.0001, respectively). Clinical features of polyploid DLBCL included reduced infiltration of extranodal sites (2/15, 13 %) and major lymph node infiltration. Of seven cases that received chemotherapy, six responded to treatment and survived. Our results suggest that polyploid DLBCL represents a clinicopathologically characteristic group of DLBCL. This knowledge can be useful for informing more personalized and targeted management of DLBCL patients.